Analisis Kualitas Pelayanan Perizinan melalui Online Single Submission pada Dinas Penanaman Modal Dan Pelayanan Perizinan Terpadu Satu Pintu Kota Binjai - Eko Prasetio; Isnaini Isnaini; Adam Adam (Universitas Medan Area, 2021)
The implementation of licensing services through Online Single Submission (OSS) at the Binjai City Investment Service and One-Stop Integrated Licensing Service (DPMPPTSP) can still be said to be unsatisfactory because it still has problems in licensing services, especially Construction Services Business Permit (IUJK) services. Problems that are often faced include the completion of the Construction Service Business Permit (IUJK) not on time and business actors do not understand the operation of the OSS system, which results in licensing services through the OSS not yet maximized. This study is to determine the quality of licensing services through OSS at the DPMPPTSP Binjai City and to find out the inhibiting factors for the implementation of licensing through OSS at the Binjai City DPMPPTSP. This research method uses a descriptive method with a qualitative approach. The results of this study indicate the quality of licensing services through OSS at DPMPPTSP of Binjai City which is examined from the dimensions of service quality, namely Tangible, Reliability, Responsiveness, Assurance ( guarantee), Empathy (empathy) as a whole is considered good but not optimal. The DPMPPTSP Of Binajai City is expected to have a technical team located at the Dinas and Dinas to conduct socialization regarding the use of the OSS system to the public so that the public is able to register their own permits and not through third parties/brokers.